Nieves penitentes are a new habitat for snow algae in one of the most extreme high-elevation environments on Earth. Issue 1 (1st January 2019) - Vimercati, Lara; Solon, Adam J.; Krinsky, Alexandra; Arán, Pablo; Porazinska, Dorota L.; Darcy, John L.; Dorador, Cristina; Schmidt, Steven K.
ABSTRACT: Nieves penitentes are pinnacle-shaped ice structures found at high elevations in the dry Andes. Here we report, using molecular and microscopic approaches, the first description of snow algae communities inhabiting penitente ice at 5, 277 m a.s.l., demonstrating a new habitat for snow algae in one of the most extreme environments on Earth. Red ice patches on penitentes contained a microbial community dominated by algae in the genera Chlamydomonas and Chloromonas, both of which were closely related to known snow algae from alpine and polar environments. In contrast, we obtained few snow algae sequences from clear ice, but we did find cyanobacteria sequences and evidence of aeolian-deposited organic matter. Tephra ("soil") within and just downhill from the penitente field hosted more complex bacterial and eukaryotic communities that were significantly different from ice communities in terms of both alpha and beta diversity. In this environment penitentes provide both water and shelter from harsh winds, high UV radiation, and thermal fluctuations, creating an oasis in an otherwise extreme landscape. Intriguingly, recent planetary investigations have suggested the existence of penitente-like structures on other planetary bodies of our solar system. Therefore, penitentes and the harsh environment that surrounds them provide a new terrestrial analog for astrobiological studies of life beyond Earth.